Populizm lewicowy w Europie na przykładzie partii „Die Linke” w Republice Federalnej Niemiec - Kopka, Artur (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
One of the main challenges European democracy has faced recently is growing political radicalism, and primarily the increasing importance of populist parties originating from both left and right sides of the political arena. This paper refers to the theoretical assumptions concerning this phenomenon to analyze the operations of the ‘Die Linke’ party in the German party system. This party is an excellent example of taking skillful advantage of the circumstances favoring the development of the populist tendencies that have emerged following the recent, radical, social, and political changes in the Federal Republic of Germany. Against the background of European extremist left-wing parties, the paper presents the influence this Left-Wing Party exerts on the changing balance of power on the German political arena on a regional and national level, the ideological profile and party platform, and the changing structure of both its members and voters.